Generative AI for Students: Inovasi Pembelajaran Digital untuk Peningkatan Pemahaman dan Manfaatnya bagi Mahasiswa - Okky Putra Barus; Yugopuspito, Pujianto; Pangaribuan, Jefri Junifer; Romindo, Romindo (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of artificial intelligence (AI) technology demands increased AI literacy among students. Generative AI, as a growing branch of AI, offers great potential to transform the learning process. Unfortunately, the level of AI literacy in Indonesia is still low. The study "The ASEAN Digital Generation Report 2023" by Kearney shows that Indonesia ranks 4th out of 6 Southeast Asian countries in readiness to face the AI era. In response, a team of lecturers from Universitas Pelita Harapan (UPH) developed a digital learning program called "Generative AI for Students." This program aims to improve students' understanding of the concepts, applications, and tools of Generative AI, especially in the academic context. This program's development uses the ADDIE method, which includes analysis, design, development, implementation, and evaluation. The "Generative AI for Students" program is implemented through the SPADA platform, utilizing features such as the Learning Management System (LMS), discussion forums, and quizzes. The evaluation results show that this program has succeeded in increasing students' understanding of Generative AI. This is indicated by an increase in post-test scores and a high level of participant satisfaction. The "Generative AI for Students" program positively increases AI literacy and equips students with skills relevant to technological developments.